Role of bilirubin overproduction in revealing Gilbert's syndrome: is dyserythropoiesis an important factor?. Issue 9 (September 1978) - Metreau, J M; Yvart, J; Dhumeaux, D; Berthelot, P
Abstract : Gilbert's syndrome was diagnosed in 37 patients with unconjugated hyperbilirubinaemia without overt haemolysis or structural liver abnormality, who had a marked reduction in hepatic bilirubin UDP-glucuronosyltransferase activity (B-GTA) (as compared with that of 23 normal subjects). No significant correlation existed in these patients between serum bilirubin level and the values of B-GTA, thus suggesting that factors other than a low B-GTA must influence the degree of hyperbilirubinaemia in Gilbert's syndrome. Studies of 51Cr erythrocyte survival and 59Fe kinetics in 10 unselected patients demonstrated slight haemolysis in eight, whereas mild ineffective erythropoiesis was suggested in all from a low 24-hour incorporation of radioactive iron into circulating red cells. This overproduction of bilirubin resulting from mild haemolysis and perhaps dyserythropoiesis might reflect only an extreme degree of the normal situation. It certainly contributes to the hyperbilirubinaemia of Gilbert's syndrome and may play a major role in the manifestation of this condition.